Multiple ecosystem services provision and biomass logistics management in bioenergy buffers: A state-of-the-art review. (June 2017) - Ferrarini, Andrea; Serra, Paolo; Almagro, María; Trevisan, Marco; Amaducci, Stefano
Abstract: Bioenergy buffers are linear landscape elements cultivated with perennial herbaceous or woody biomass crops placed along arable field margins and watercourses. This systematic review evaluates the potential impact of bioenergy buffers on multiple ecosystem services (ES) provision while describing key factors along the biomass supply chain. An Impact Assessment (IA) methodology was adopted to capture the direction and the level of confidence of impact on multiple ES including regulating (climate, water and biodiversity), supporting (soil health) and provisioning services (biomass and energy yield). The IA revealed that the implementation of bioenergy buffers on previous croplands rather than on grasslands sustains long-term provision of multiple ES such as climate, water quality and biodiversity regulation and soil health. Herbaceous buffers were found to be more effective than woody buffers in the provision of multiple ES. Knowledge gaps relative to climate and water quality regulation services were identified for the establishment phase of bioenergy buffers (0-3y). Regarding biomass logistics, the limited operating space for farm machinery was the main shortcoming when comparing bioenergy buffers to large-scale bioenergy plantations. The intra- and inter-farm spatial fragmentation of biomass supply areas may increase environmental costs related to biomass collection and transport operations, but this has not yet been fully tested. Establishing a network of bioenergy buffers increases landscape connectivity and the overall area of ES provision in the agricultural landscape. Payments for ES obtained from bioenergy buffers can ultimately improve the economics of sustainable bioenergy and help achieving environmental goals of EU policies on water, soil and biodiversity protection. Graphical abstract: